Migration and Occupation in the Brazilian Labor Market - Luís Abel da Silva Filho (Revista Facultad de Ciencias Económicas, 2021)
Individuals’ socioeconomic and demographic characteristics have always impacted their occupation. However, few empirical studies with census data have researched how migration af- fects occupation. Therefore, this paper aims to analyze the determining factors of occupation in migrants and non-migrants aged 15 to 60 years in Brazilian municipalities. The data are taken from 2000 and 2010 Brazilian Demographic Censuses. The literature is reviewed, and then multinomial logistic regressions are used. The results show that fixed-date inter-municipal migrants in Brazil experience worse forms of insertion in the labor market than non-migrants in both censuses under analysis.